Chitosan composite films: physicochemical characterization and their use as coating in papaya Maradol stored at room temperature - Figueroa, Miguel Salvador-; López, Dafne Castillo-; Anaya, Lourdes Adriano-; López, Didiana Gálvez-; Quijano, Raymundo Rosas-; Ovando, Alfredo Vázquez- (Emirates Journal of Food and Agriculture, 2017)
The main objectives of this study were; first formulate and evaluate some properties of chitosan composite films enriched with essential oils of cinnamon, thyme, clove, and lime alone or in combination; and second select the most appropriate formulation and evaluate their effect on physiological properties and fungal incidence of papaya Maradol stored at environmental tropical conditions. Breaking strength, thickness, color, moisture, water vapor permeability, solubility and water sorption of films were measured. Furthermore, in vitro activity was evaluated against Colletotrichum gloeosporioides Penz. Using multivariate analysis and based on the most desirable characteristics (low water sorption values, water vapor permeability, solubility, and greater inhibition of C. gloeosporioides), three formulations of films were used lately for coated fruit of papaya Maradol and stored at 28 ± 2 °C and 85 % RH. Two control treatments were included: one uncoated and other treated with Mancozeb® fungicide. At six days of storage, the fruit of both control treatments showed evident signs of ripening; contrary to the treatments wherein fruit were coated, and had low respiration, other attributes as firmness, little change in the external color of the fruit were manifested. Similarly, the use of composite films reduced the fungus C. gloeosporioides by 30-50 %. The use of film enriched with essential oil of 1 % cinnamon- 1 % thyme improved the characteristics of fruit quality, increased shelf life and reduced by 50 % the incidence of fungus in papaya Maradol stored under humid tropic environmental conditions. This coating can be an alternative to potentially reduce the need for cold storage during postharvest handling.